Changes During Incubation Within Double-Yolked Duck (Anas platyrhynchos domesticus) Eggs: Yolk Position, Mortality, Hatchability and the Importance of an Optimal Egg Size - Salamon , Attila; Kent, John P. (International Journal of Poultry Science, 2014)
Double-yolked (DY) and single-yolked (SY) duck eggs (n = 1318 for both) were candled and weighed on Days (d) 2, 8, 12, 15, 19, 22 and 25 of incubation and yolk/embryo position was recorded on d2, d8 and at post-mortem. From d8 only eggs with live fertile yolk(s) remained in the incubator. On d2, 99.39% of yolks in DY eggs were in the adjacent position and by d8 yolk positions changed to parallel position in DY1F (one fertile yolk) and DY2F (two fertile yolks) eggs, 14.1 and 88.62%, respectively (pd22) embryonic mortality was significantly higher in DY compared to SY eggs (p